Comparative Analysis of Muhammad Umer Chapra and John Maynard Keynes' Perspectives on Fiscal Stimulus in Addressing Economic Crises - Arifin, Zainal; Prayitno, Mustofa Aji; Sudarmanto, Eko (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
This article presents a comprehensive comparative analysis of the economic perspectives of Muhammad Umer Chapra, an esteemed Islamic economist, and John Maynard Keynes, a renowned Western economist, concerning the concept of fiscal stimulus as an effective measure to address economic crises. By examining their viewpoints, the article explores the divergent approaches and underlying principles in implementing fiscal stimulus policies. Chapra's perspective highlights the importance of ethics, justice, and social welfare in economic decision-making, emphasizing the compatibility of fiscal stimulus with Islamic economic principles. In contrast, Keynesian economics, as advocated by Keynes, emphasizes the role of government intervention and the use of fiscal policies to stimulate aggregate demand and overcome economic downturns. The article critically analyzes the similarities, differences, and potential areas of convergence between these two prominent economists, shedding light on the implications and effectiveness of fiscal stimulus measures in various economic contexts. By understanding and comparing these perspectives, policymakers and economists can gain valuable insights into crafting comprehensive and context-specific approaches to address economic crises and promote sustainable economic growth.